Effects of magnetohydrodynamics and velocity slip on mixed convective flow of thermally stratified ternary hybrid nanofluid over a stretching/shrinking sheet - Ishak, Anuar; Waini, Iskandar; Jamrus, Farah Nadzirah; Khan, Umair (Elsevier Ltd, 2024)
This paper undertakes a numerical exploration into the dynamics of fluid flow and heat transfer within the stagnation region of a mixed convection scenario involving thermally stratified ternary hybrid nanofluid. The study incorporates the impact of a magnetohydrodynamic and velocity slip, while also considering a permeable sheet that can stretch or shrink. The equations governed the f low problem are transformed into similarity equations using a similarity transformation. Then the similarity equations are solved utilizing the built in solver (bvp4c) in MATLAB. This flow problem has two solutions, as expected. Following that, the outcomes of the stability analysis show the viability and physical robustness of the first solution. Additionally, the study identifies magnetic, suction, and volume fraction as parameters capable of delaying turbulence onset in the boundary layer. Moreover, the heat transmission of the ternary hybrid nanofluid is enhanced by an increased volume fraction. It is important to note that the reported results specifically pertain to the combination of alumina, copper, and titania nanoparticles. Different combinations of nanoparticles may exhibits unique properties related to both flow behaviour and heat transmission.